Association between 24‐hour combined multichannel intraluminal impedance‐pH monitoring and symptoms or quality of life in patients with laryngopharyngeal reflux. (8th January 2017) - Kim, S.I.; Kwon, O.E.; Na, S.Y.; Lee, Y.C.; Park, J.M.; Eun, Y.G.
Abstract : Objective: To evaluate the association between the parameters of 24‐hour multichannel intraluminal impedance (MII)‐pH monitoring and the symptoms or quality of life (QoL) in laryngopharyngeal reflux (LPR) patients. Design: Prospective cohort study without controls. Setting: University teaching hospital. Methods: Forty‐five LPR patients were selected from subjects who underwent 24‐hour MII‐pH monitoring and were diagnosed with LPR from September 2014 to May 2015. Reflux Symptom Index (RSI), Health‐related Quality of Life (HRQoL), Short Form 12 (SF‐12) Survey questionnaires were surveyed. Spearman's correlation was used to analyse the association between the symptoms or QoL and 24‐hour MII‐pH monitoring. Results: Most parameters in 24‐hour MII‐pH monitoring showed weak or no correlation with RSI, HRQoL and SF‐12. Only number of non‐acid reflux events that reached the larynx and pharynx (LPR‐non‐acid) and number of total reflux events that reached the larynx and pharynx (LPR‐total) parameters showed strong correlation with heartburn in RSI ( R = 0.520, P < 0.001, R = 0.478, P = 0.001, respectively). Multiple regression analysis showed that there was only one significant regression coefficient between LPR‐non‐acid and voice/hoarseness portion of HRQoL ( b = 1.719, P = 0.022). Conclusion: Most parameters of 24‐hour MII‐pH monitoring did not reflect subjective symptoms or QoL in patients with LPR.